Transforming Nikkeijin identity and citizenship untold life histories of Japanese migrants and their descendants in the Philippines, 1903-2013 - Ohno, Shun 1953- (Quezon City Ateneo de Manila University Press, 2015)
This is an exploration of Philippine cultural history. It presents a diverse range of texts including: the legend of a mountain goddess, Pigafetta's discovery account of the Philippines, the life of a 17th-century Christian convert and the foundation narrative of a Marian shrine.
Maps, figures and tables -- Acknowledgment -- Glossary -- Abbreviations -- Chapter 1. Introduction -- Chapter 2. The Issei Legacies, 1903-1937 -- Chapter 3. Instilling the Japanese spirit in Nisei's minds, 1937-1942 -- Chapter 4. Between father's nation and mother's nation, 1942-1945 -- Chapter 5. Rebirth as Philippine Nikkeijin, 1945-1995 -- Chapter 6. Regaining "Japaneseness," 1995-*2013 -- Chapter 7. Towards transnatinal formation of citizenship and identiy -- Appendixes -- Endnotes -- References -- Index.
Thesis (doctoral)--Australian National University, 2005.
Includes bibliographical references (pages 247-268) and index.
Keywords: Japanese -- Social life and conditions -- 1903-2013. -- Philippines; Philippines -- Emigration and immigration -- History -- 1908-2013.; Japan -- History -- 1903-2013. -- Philippines